HAMBATAN KOMUNIKASI GURU PADA PROSES PEMBELAJARAN PENDIDIKAN JASMANI DI SD NEGERI SE-KECAMATAN KEMBARAN - Yudha Febrianta; Ahmad Fauzan (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to determine the communication barriers of teachers in the physical education learning process in public elementary schools throughout the Kembaran District. This research is a descriptive study using a survey method with the data collection technique in the form of a questionnaire. The population in this study were 26 Physical Education teachers, data collection instruments using a questionnaire, data analysis techniques using descriptive analysis as outlined in the form of a percentage of teacher communication barriers to the physical education learning process in public elementary schools in Kembaran Subdistrict using 5 categories namely categories very good, good, medium, lacking, and very lacking. The results showed that the communication barriers of teachers to the physical education learning process in state elementary schools in the Kembaran sub-district were in the medium category, in detail there were 3 teachers (11.54%) in the excellent category, 3 teachers (11.54%) in the good category, 13 teachers (46.15%) in the medium category, 5 teachers (19.23%) in the poor category, 3 teachers (11.54%) in the very poor category.